1956
DOI: 10.1177/028418515604500201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urography with Selective Clearance as Tests of Renal Function

Abstract: The urographic signs of normal renal function following dehydration of the patient usually consist of simultaneous filling of the calyces on both sides, moderate distension and high density of the pelves and upper parts of the ureters upon application of ureteral compression, and bilateral emptying of the pelves and ureters after the compression is removed. If the examination provokes shock with a decrease in the systolic blood pressure to 70 mm Hg, contrast filling of the pelves does not commence, or ceases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1958
1958
1960
1960

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In one of the cases, for instance, satisfactory urograms were obtained where a clearance examination showed that both the filtration and tubular excretion were reduced by 70 per cent. According to studies by EDLING and co-workers (9), this may be ascribed to the fact that the urographie examination is a qualitative test of func tion. In spite of marked local destruction, the residual functional paren-EENAL PAPILLARY NECROSIS 265 chyma may still, to judge from the films, provide a high urine concentra tion, although this is in fact not the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the cases, for instance, satisfactory urograms were obtained where a clearance examination showed that both the filtration and tubular excretion were reduced by 70 per cent. According to studies by EDLING and co-workers (9), this may be ascribed to the fact that the urographie examination is a qualitative test of func tion. In spite of marked local destruction, the residual functional paren-EENAL PAPILLARY NECROSIS 265 chyma may still, to judge from the films, provide a high urine concentra tion, although this is in fact not the case.…”
Section: Discussionmentioning
confidence: 99%
“…At the next urographie control a year later all the papillae of the right kidney had been detached, but there was no change in the clinical picture. Where nephrectomy is to be performed it is evidently impossible to exclude papillary changes in the other kidney solely from the roentgenograms; selective clearance tests should also be performed (9). On the other hand, typical necrosis in both the medullary and papillary forms developed during the period of observation in 4 cases, and the papillae were detached without the so-called 'typical' signs appearing -even long afterwards -the clinical picture being just one of ordinary noncomplicated pyelitis or pyelonephritis.…”
Section: Methodsmentioning
confidence: 99%
“…At the next urographic control a year later all the papillae of the right kidney had been detached, but there was no change in the clinical picture. Where nephrectomy is to be performed it is evidently impossible to exclude papillary changes in the other kidney solely from the roentgenograms; selective clearance tests should also be performed (9). On the other hand, typical necrosis in both the medullary and papillary forms developed during the period of observation in 4 cases, and the papillae were detached without the so-called 'typical' signs appearingeven long afterwardsthe clinical picture being just one of ordinary noncomplicated pyelitis or pyelonephritis.…”
Section: Materinlmentioning
confidence: 99%
“…The analytic methods of clearance determination were described by EDVALL (1958). Samples of urine were obtained by bladder catheterization.…”
mentioning
confidence: 99%